Interaction of human neutrophils with endothelial cells regulates the expression of endogenous proteins annexin 1, galectin-1 and galectin-3 - Gil, C. D.; La, M.; Perretti, M.; Oliani, S. M. (Elsevier B.V., 2006)
Annexin 1 (ANXA1), galectin-1 (Gal-1) and galectin-3 (Gal-3) proteins have been identified as important mediators that promote or inhibit leukocyte migration. The expression of these proteins was studied in human neutrophils and endothelial cells (ECs) during a transmigration process induced by IL-8. Upon neutrophil adhesion to EC, a significant increase in the cleaved ANXA1 (LCS3, raised against all ANXA1 isoforms) expression was detected in the plasma membrane of adhered neutrophils and ECs compared to intact ANXA1 isoform (LCPS1, against N-terminus of protein). Adherent neutrophils had elevated Gal-3 levels in the nucleus and cytoplasm, and ECs in their plasma membranes. In contrast, a decrease in the total amounts of Gal-1 was detected in migrated compared to non-migrated neutrophils. Therefore, ANXA1 and Gal-3 changed in their content and localization when neutrophils adhere to endothelia, suggesting a process of sensitive-balance between two endogenous anti- and pro-inflammatory mediators. (c) 2006 International Federation for Cell Biology. Published by Elsevier Ltd. All rights reserved.
Keywords: annexin; galectin; Ea.hy926 cells; transmigration assay; immunogold electron microscopy